2012
DOI: 10.1002/acr.20663
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity and foot pain and its association with fat mass, fat distribution, and muscle mass

Abstract: Objective. To examine the relationship between obesity, body composition, and foot pain as assessed by the Manchester Foot Pain and Disability Index (MFPDI). Methods. Subjects 25-62 years of age (n ‫؍‬ 136) were recruited as part of a study examining the relationship between obesity and musculoskeletal health. Foot pain was defined as current foot pain and pain in the last month, and an MFPDI score of >1. Body composition (tissue mass and fat distribution) was measured using dual x-ray absorptiometry. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
3
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 37 publications
7
82
3
5
Order By: Relevance
“…These findings corroborate Larsson's conclusion that high BMI value, age and lower body pain could predict functional limitations in obese women (25). Furthermore, it has been demonstrated that increased BMI is strongly associated with foot pain and disability, and this may impair both biomechanical and metabolic mechanisms (26).…”
Section: Pain and Quality Of Life In Obese Patientssupporting
confidence: 79%
“…These findings corroborate Larsson's conclusion that high BMI value, age and lower body pain could predict functional limitations in obese women (25). Furthermore, it has been demonstrated that increased BMI is strongly associated with foot pain and disability, and this may impair both biomechanical and metabolic mechanisms (26).…”
Section: Pain and Quality Of Life In Obese Patientssupporting
confidence: 79%
“…A recent study found that both BMI and FMI were independent predictors of prevalent foot pain, suggesting there are likely both biochemical and biomechanical factors in the development of foot pain (3). Results of the current study also support the utility of FMI, with BMI losing its significance when fat mass was added to the multivariate model.…”
Section: Discussionsupporting
confidence: 80%
“…In overweight and obese individuals, changes in their foot shape were observed due to excessive biomechanical loading and pressure (Crosbie & Burns 2008;Silveri 2015). In addition, foot pain was reported as a common problem in overweight and obese individuals (Butterworth et al 2012;Tanamas et al 2012). Overweight and obese individuals with either flat arch or high arch are at high risk of getting foot injuries and foot pain (Domjanic et al 2013).…”
Section: Introductionmentioning
confidence: 99%